The Urgency of Religion and Culture in STEM (Science, Technology, Engineering, Mathematics) Based Learning Models: Meta Data Analysis - Asiyah Asiyah; Ahmad Walid; Raden Gamal Tamrin Kusumah (Postgraduate, University of Mataram, 2023)
The aims of this research is to synthesize literature studies in order to answer the following questions: How important is religion? knowledge and cultural studies in studying science and the relationship between religion, culture and STEM education. This type of research is a literature study. The research method was to synthesize this literature following several steps to ensure the validity of the results. The results obtained indicate that the development of scientific literacy skills in education needs to be based on ethnographic-religious study-based learning. When students are invited to see the natural surroundings of phenomena including local culture, indirectly students will be invited to think literally about science. Various studies have proven that ethnoscience-based learning can help students to improve students' scientific literacy skills and this is an update in this research. The urgency of religious and cultural studies in education is of concern to educators and researchers